Nonunion Employee Representation: Theory and the German Experience with Mandated Works Councils - Uwe Jirjahn; Stephen C. Smith (Institute of Labor Economics (IZA), 2017)
Theories of how nonunion employee representation impacts firm performance, affects market equilibria, and generates externalities on labor and society are synthesized. Mandated works councils in Germany provide a particularly strong form of nonunion employee representation. A systematic review of research on the German experience with mandated works councils finds generally positive effects, though these effects depend on a series of moderating factors and some impacts remain ambiguous. Finally, key questions for empirical research on nonunion employee representation, which have previously been little analyzed in the literature, are reviewed.
Keywords: J50; M50; 330; nonunion representation; works councils; organizational failures; market failures; society